Reduction of parasitic nematode by soil solarization in transplanted aman rice-wheat system (Bangladesh Journal of Agricultural Research, 2008)
Experiments were conducted to study the effect of soil solarization on soil nematode, weed, yield contributing characters, and grain yield of transplanted aman rice and also to observe the residual effect of the treatments on the following wheat crop. The treatments were, untreated control (T1), Furadan 5G (Carbofuran) @ 18 kg/ha (T2), soil solarization using transparent plastic (25µm) for 4 weeks and spaded after solarization to disturb the soil (T3), soil solarization using transparent plastic (25µm) for 4 weeks and not spaded after solarization (undisturbed) (T4), and plastic mulch (land covered by transparent plastic (25µm) throughout the aman rice season) (T5). The application of plastic mulch (T5) significantly increased plant height, number of tiller per m2, and number of panicles per m2 reduced weed, galling incidence, and parasitic nematode population in soil. The highest increase of grain yield (26.77%) was observed in T5 over control. Residual effect of those treatments of aman crop was also effective in reducing nematode in soil and root gall in wheat crop. Those residual effect of treatments also significantly increased yield of wheat. Seven parasitic nematode species, Tylenchorynchus sp., Hirschmaniella sp., Heterodera sp., Pratylenchus sp., Tylenchus sp., Xiphinema sp. and Meloidogyne sp. were found both in rice and wheat field. Different parasitic nematode species decreased due to the treatments over control in aman and wheat fields.Bangladesh J. Agril. Res. 32(4) : 533-540